Tren Perubahan Sosial: Transgresi dan Inovasi dalam Gaya Sastra Kontemporer - Alanshor, Ibnu Adil; Syahid, Ahmad Habibi (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2023)
The social changes that have occurred in the Arab world in the modern era have greatly influenced changes in contemporary literary styles, this has raised many questions about how contemporary literary styles are influenced by the social changes currently occurring. This research aims to discuss the influence of social changes occurring in modern society on contemporary literary styles, as well as find out what factors can influence contemporary literary styles. The method that will be used in this research is the qualitative descriptive method, with this method it is hoped that readers can understand the discussion in this research through the images that will be presented more clearly, while the qualitative approach is used because it is often used in humanities, social sciences, and research. other things that cannot be explained using numbers. Meanwhile, the data collection used in this research used the Literature Study method, where this research obtained data sources from several written works such as books, song lyrics, and articles and journals related to the theme of this research. The results of the research in this article show that social changes have a great influence on contemporary literary styles, giving birth to new genres in literary works. This occurs as a result of reflection on the social conditions that existed in the era in which the literary work was born because in reality literary works are not born from emptiness, but written in the social context in which the literary work was created.